2009
DOI: 10.1136/bcr.07.2009.2061
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric sequelae in an efavirenz treated patient with hepatitis B

Abstract: We report the case of a 34-year-old man of African origin, positive for both HIV and hepatitis B virus, who developed symptoms of mania and psychosis while being treated with efavirenz (a non-nucleoside reverse transcriptase inhibitor used in HIV therapy) that required inpatient psychiatric admission and treatment with antipsychotic medication. Our case illustrates multiple predisposing and precipitating factors occurring simultaneously that have been previously implicated individually in the development of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…One study reported that mild neuropsychiatric symptoms persisted for up to 3 years in many patients [8]. Early severe neuropsychiatric symptoms usually resolve on discontinuation of efavirenz [9][10][11][12][13][14]. A recent case report of vacuolar axonopathy leading to a depressed level of consciousness, aspiration pneumonia and death was thought to be efavirenz induced, suggesting that efavirenz neurotoxicity may on occasion be more severe than transient neuropsychiatric effects [15].…”
Section: Introductionmentioning
confidence: 98%
“…One study reported that mild neuropsychiatric symptoms persisted for up to 3 years in many patients [8]. Early severe neuropsychiatric symptoms usually resolve on discontinuation of efavirenz [9][10][11][12][13][14]. A recent case report of vacuolar axonopathy leading to a depressed level of consciousness, aspiration pneumonia and death was thought to be efavirenz induced, suggesting that efavirenz neurotoxicity may on occasion be more severe than transient neuropsychiatric effects [15].…”
Section: Introductionmentioning
confidence: 98%
“…[22][23][24] There have been a number of reports of psychosis or mania (after an overdose) developing in patients without SMI in a temporal relationship to starting ART with EFV. 22,[25][26][27][28][29][30][31][32][33] High serum levels of EFV related to genetic factors have been implicated in the development of psychosis, 27,29,30 but this has not been borne out in longitudinal studies. [22][23][24]34 Other antiretroviral drugs, including ZDV, abacavir (ABC), and NVP, have also been implicated in the development of psychosis by temporal association.…”
Section: Discussionmentioning
confidence: 99%
“…Efavirenz-induced psychosis has been reported in patients as young as 12 years of age. The general consensus is that efavirenz may alter cytokine levels that may contribute to the development of these psychiatric symptoms (Salter & Patel 2009). The CD4 lymphocyte counts as well as the 'viral load' have a significant influence on the severity of these psychiatric effects.…”
mentioning
confidence: 99%